1992
DOI: 10.1029/91jd03044
|View full text |Cite
|
Sign up to set email alerts
|

An intercomparison of surface energy flux measurement systems used during FIFE 1987

Abstract: During FIFE 1987, surface energy fluxes were measured at 22 flux sites by nine groups of scientists using different measuring systems. A rover Bowen ratio station was taken to 20 of the flux stations to serve as a reference for estimating the instrument‐related differences. The rover system was installed within a few meters from the host instrument of a site. Using linear regression analysis, net radiation, Bowen ratio, and latent heat fluxes were compared between the rover measurements and the host measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 6 publications
4
24
1
Order By: Relevance
“…During the FIFE experiment, Nie et al (1992) found that the four flux components measured by an EC system summed to a maximum residual of 160 W m −2 . An EC system and EBBR system were collocated at site 926 for 3 days.…”
Section: Review Of Surface Flux Measurements and Energy-balance Closurementioning
confidence: 99%
See 1 more Smart Citation
“…During the FIFE experiment, Nie et al (1992) found that the four flux components measured by an EC system summed to a maximum residual of 160 W m −2 . An EC system and EBBR system were collocated at site 926 for 3 days.…”
Section: Review Of Surface Flux Measurements and Energy-balance Closurementioning
confidence: 99%
“…The importance of accurate micrometeorological measurements of surface fluxes is a justification for long-term flux measurement networks (Baldocchi et al, 1996). Unfortunately, the micrometeorological literature contains numerous anecdotal references to possible systematic underestimates of surface scalar fluxes by the preferred measurement system; namely eddy covariance (Dugas et al, 1991;Nie et al, 1992;Fritschen et al, 1992;Goulden et al, 1997;McCaughey et al, 1997;Mahrt, 1998). The potential problems that systematic errors can create in long-term surface flux measurements, particularly selective systematic errors (different daytime errors from night-time errors), are considered by Moncrief et al (1996) and can be serious.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the observed net radiation is usually greater than the sum of the observed sensible heat, the latent heat and the surface soil heat. Nie et al (1992) found that the maximum residual energy could reach 160 Wm À2 during the First ISLSCP (International Satellite Land Surface Climatology Project) Field Experiment (FIFE), and that eddy correlation systems gave slightly lower latent heat fluxes in comparison with the Bowen ratio systems. McCaughey et al (1997) reported that the average daily energy budget closure ðH þ lEÞ/ ðR n À G 0 Þ varied from 0.85 to 0.95 for forest sites of the BOREAS (Boreal EcosystemAtmosphere Study) experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The closure issue becomes even more important upon consideration of the long-term water balance. Twine et al (2000) summed over a period of 15 days from 4 EC systems and drew a conclusion that evapotranspiration would be significantly overestimated by calculating LE as the residual of the energy budget; this is also supported by others (Dugas et al 1991;Kampf et al 2005;Nie et al 1992). Thus, in our study, it is a risk to use the EC residual method to estimate LE since there were more uncertainties from R n , G, S, and other heat sinks, especially when LE is smaller or under a certain spatial scale.…”
Section: Potential Causes Of R N Measurements For Non-closurementioning
confidence: 70%